2008
DOI: 10.1007/s00383-008-2174-0
|View full text |Cite
|
Sign up to set email alerts
|

The rationale for the use of parenteral omega-3 lipids in children with short bowel syndrome and liver disease

Abstract: Parenteral nutrition associated liver disease (PNALD) is the major source of morbidity and mortality in children with short bowel syndrome (SBS). There is emerging evidence that omega-6 fatty acids (omega6FA) within the parenteral solution play a major role in PNALD and their effects may be reversed or ameliorated by substitution with omega-3 fatty acids (omega3FA). This paper reviews the mechanisms whereby omega3FAs may influence PNALD by improving bile flow, inhibiting steatosis, and having immunomodulatory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
66
0
4

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 86 publications
(70 citation statements)
references
References 50 publications
0
66
0
4
Order By: Relevance
“…The authors themselves, however, substituted Intralipid Ò with Omegaven Ò in short bowel syndrome patients with advanced liver disease and concluded that Omegaven Ò has the ability to restore liver function without complications or mortality [1]. Furthermore, they ''rescued'' eight of 12 patients with Omegaven Ò alone [1,6]. In a prospective case series of 18 consecutive patients, which was published in the journal Pediatrics the month prior to the authors' manuscript submission, we have demonstrated that patients on Omegaven Ò experienced from adequate to improved growth and did not have signs of coagulopathy or EFAD 30 days after initiation of therapy [3].…”
Section: Dear Editormentioning
confidence: 95%
See 2 more Smart Citations
“…The authors themselves, however, substituted Intralipid Ò with Omegaven Ò in short bowel syndrome patients with advanced liver disease and concluded that Omegaven Ò has the ability to restore liver function without complications or mortality [1]. Furthermore, they ''rescued'' eight of 12 patients with Omegaven Ò alone [1,6]. In a prospective case series of 18 consecutive patients, which was published in the journal Pediatrics the month prior to the authors' manuscript submission, we have demonstrated that patients on Omegaven Ò experienced from adequate to improved growth and did not have signs of coagulopathy or EFAD 30 days after initiation of therapy [3].…”
Section: Dear Editormentioning
confidence: 95%
“…The authors themselves, however, substituted Intralipid Ò with Omegaven Ò in short bowel syndrome patients with advanced liver disease and concluded that Omegaven Ò has the ability to restore liver function without complications or mortality [1]. Furthermore, they ''rescued'' eight of 12 patients with Omegaven Ò alone [1,6].…”
Section: Dear Editormentioning
confidence: 98%
See 1 more Smart Citation
“…Zulfakar, Edwards, and Heard (2007) have reviewed the works that have examined the potential use of n−3 PUFA in psoriasis. Several recent reviews have studied the influence of omega-3 PUFA on bowel diseases (Razack & Seidner, 2007;Diamond, Sterescu, Pencharz, & Wales, 2008;Turner, Zlotkin, Shah, & Griffiths, 2008). The application of omega-3 fatty acids in the treatment and prevention of mental illnesses (Horrobin, Manku, Hillman, Iain, & Glen, 1991;Stillwell & Wassall, 2003;McNamara, 2006;Clayton, Hanstock, Garg, & Hazell, 2007;Mazza, Pomponi, Janiri, Bria, & Mazza, 2007;Ross, Seguin, & Sieswerda, 2007;Song & Zhao, 2007) and on the prevention of several types of cancer (MacLean et al, 2006;Chen et al, 2007;Calviello, Serini, & Piccioni, 2007) has also been widely reviewed.…”
Section: Omega-3 Fatty Acids and Human Healthmentioning
confidence: 99%
“…Third-generation lipid emulsions contain soybean oil for the supply of essential fatty acids, medium-chain triglycerides for rapid provision of energy, olive oil to reduce the n–6:n–3 ratio and to supply vitamin E, and fish oil for its anti-inflammatory effects. Beneficial effects of these mixtures on liver function and serum triglycerides have been described in various studies, including children [39,40]. Whether they will also increase the tolerance to parenteral substrates in preterm neonates is being investigated in several ongoing trials.…”
Section: Managing Nutrition According To the Latest Guidelines Of Thementioning
confidence: 99%